2020
DOI: 10.1245/s10434-020-08268-1
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation and Outcome in 2295 Patients with Stage I–III Colorectal Cancer from Scotland and Norway: First Results from the ScotScan Colorectal Cancer Group

Abstract: Background. Systemic inflammatory response (SIR) is an adverse prognostic marker in colorectal cancer (CRC) patients. The ScotScan Colorectal Cancer Group was established to examine how markers of the SIR differ between populations and may be utilised to guide prognosis. Patients and Methods. Patients undergoing resection of stage I-III CRC from two prospective datasets in Scotland and Norway were included. The relationship between the modified Glasgow Prognostic Score (mGPS; combination of C-reactive protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Accumulating evidence has revealed that cancer-associated systematic inflammation might play crucial roles in the genesis and progression of tumors [ 7 10 ]. The inflammatory response is known to be reflected by many blood biomarkers, including neutrophil lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), and lymphocyte monocyte ratio (LMR).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has revealed that cancer-associated systematic inflammation might play crucial roles in the genesis and progression of tumors [ 7 10 ]. The inflammatory response is known to be reflected by many blood biomarkers, including neutrophil lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), and lymphocyte monocyte ratio (LMR).…”
Section: Introductionmentioning
confidence: 99%
“…A unique discovery from our investigations was that sex differences associated with the vitamin D status also pertained to the modes of systemic inflammation. The clinical syndrome of SIR, defined by elevated circulating white blood cell-and thrombocyte counts and acutephase proteins such as C-reactive protein [35], has been consistently observed to confer poor outcome [36], as shown valid in all stages of CRC [8,9]. In the present study population, the classic SIR was related to low vitamin D in the male patients, also when the associations were compared by entering sex and 25(OH) D level as interacting factors in the statistical model.…”
Section: Discussionmentioning
confidence: 95%
“…A wide range of molecular components, many of which are reflected in the systemic circulation, are involved in cancer-related inflammation [7]. The systemic inflammatory response (SIR) as such is an adverse prognostic marker in all stages of CRC [8,9]. Furthermore, it is notable that both incidence and mortality rates of rectal cancer are significantly higher in men than in women [10,11], which might relate to modifiable lifestyle factors with different impact in the two sexes [12].…”
Section: Introductionmentioning
confidence: 99%
“…A unique discovery from our investigations was that sex differences associated with the vitamin D status also pertained to the modes of systemic inflammation. The clinical syndrome of SIR, defined by elevated circulating white blood cell- and thrombocyte counts and acute-phase proteins such as C-reactive protein [ 35 ], has been consistently observed to confer poor outcome [ 36 ], as shown valid in all stages of CRC [ 8 , 9 ]. In the present study population, the classic SIR was related to low vitamin D in the male patients, also when the associations were compared by entering sex and 25(OH) D level as interacting factors in the statistical model.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of molecular components, many of which are reflected in the systemic circulation, are involved in cancer-related inflammation [ 7 ]. The systemic inflammatory response (SIR) as such is an adverse prognostic marker in all stages of CRC [ 8 , 9 ]. Furthermore, it is notable that both incidence and mortality rates of rectal cancer are significantly higher in men than in women [ 10 , 11 ], which might relate to modifiable lifestyle factors with different impact in the two sexes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%